Diplofuranones A and B , two further new 4-monosubstituted 2 ( 3H ) -dihydrofuranones produced by Diplodia corticola , a fungus pathogen of cork oak - Evidente, Antonio; Andolfi, Anna; Fiore, Michele; Spanu, Emanuela (ARKIVOC, 2007)
Two new 4-monosubstituted 2(3H)-dihydrofuranones, named diplofuranones A and B, were isolated from liquid cultures of Diplodia corticola, a plant pathogenic fungus causing a canker disease of cork oak (Quercus suber L.). The same fungus also produces several metabolites such as the diplopyrone, the (3S,4R)-trans- and the (3R,4R)-cis-4-hydroxymellein, the sapinofuranone B and its (S,S)-enantiomer, the well known sphaeropsidins A-C, and the diplobifuranylones A and B. The diplofuranones A and B were characterised, using spectroscopic (essentially NMR and MS techniques) methods, as the 4-[(1E,3E)-5-hydroxyhexadienyl]butan-4-olide and its corresponding 3,4-dihydro side chain derivative. The stereochemistry of the stereogenic secondary hydroxylated carbon of the side chain of diplofuranone A was determined by application of Mosher’s method and proved to be R. Diplofuranone A tested at 0.2 mg mL-1 on non-host plant did not show phytotoxic activity.
Keywords: canker disease; Cork oak; Diplodia corticola; phytotoxic metabolites; Quercus suber L.

Diplofuranones A and B , two further new 4-monosubstituted 2 ( 3H ) -dihydrofuranones produced by Diplodia corticola , a fungus pathogen of cork oak - Evidente, Antonio; Andolfi, Anna; Fiore, Michele; Spanu, Emanuela (ARKIVOC, 2007)
Two new 4-monosubstituted 2(3H)-dihydrofuranones, named diplofuranones A and B, were isolated from liquid cultures of Diplodia corticola, a plant pathogenic fungus causing a canker disease of cork oak (Quercus suber L.). The same fungus also produces several metabolites such as the diplopyrone, the (3S,4R)-trans- and the (3R,4R)-cis-4-hydroxymellein, the sapinofuranone B and its (S,S)-enantiomer, the well known sphaeropsidins A-C, and the diplobifuranylones A and B. The diplofuranones A and B were characterised, using spectroscopic (essentially NMR and MS techniques) methods, as the 4-[(1E,3E)-5-hydroxyhexadienyl]butan-4-olide and its corresponding 3,4-dihydro side chain derivative. The stereochemistry of the stereogenic secondary hydroxylated carbon of the side chain of diplofuranone A was determined by application of Mosher’s method and proved to be R. Diplofuranone A tested at 0.2 mg mL-1 on non-host plant did not show phytotoxic activity.
Keywords: canker disease; Cork oak; Diplodia corticola; phytotoxic metabolites; Quercus suber L.